Gastroenteroloji ve Geriatri - Özercan, Abdullah Mübin; Gümüşsoy, Mesut; Atayan, Yahya; Yalçın, Muhammed; Kıyak, Mevlüt; Üçer, Mehtap; Şentürk, Süleyman; Baykan, Ahmed Ramiz; Keçeci, Mustafa; Köseoğlu, Hüseyin; Kaya, Muhammed; Durak, İbrahim and Eminler, Ahmet Tarık and Güneri, Gökhan and Sağlam, Osman and Harı, Mustafa and Kiremitçi, Sercan and Moral, Kenan and Yanık, Sinan and Demiröz, Hakan and Bedir, Osman and İnan, Bayram and Ayhan, Mehmet Emin and Ünver, Nazmi Gökhan and Erten, Ahmet Teoman and Öztürk, Oğuz and Düzenli, Tolga and Aktaş, Levent and Değer, Özgür and Akar, Mustafa and Tosun, Mustafa and Köseoğlu, Tankut and Demirci, Selim and Keklikkıran, Çağlayan and Çatalbaş, Ramis and Ekin, Nazım and Çapar, Halil and Bulur, Atilla and Coşkun, Nurettin and Çoşkun, Orhan and Boz, Fatma Betül and Habiboğlu, İhsan and Ergül, Mücahit and Toka, Bilal and Yıldırım, Abdurrahim and Akçaer Öztürk, Nevin and Çetin, Duran Deha and Şirin, Abdullatif and Konür, Şevki and Önem, Soner and Aslanov, Seymur and Irak, Kader and Yıldız, Mehmet and Taşkıran, İsmail and; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2023)
-